Hashimoto's encephalopathy with cerebellar ataxia as the main symptom: A case report and literature review - Wei, Chunxiao; Shen, Yanxin; Zhai, Weijie; Shang, Tianling; Wang, Zicheng; Wang, Yongchun; Li, Mingxi; Zhao, Yang; Sun, Li (Frontiers in Neurology, 2022)
Hashimoto's encephalopathy (HE), also known as steroid responsive encephalopathy associated with autoimmune thyroiditis (SREAT), has a variety of clinical manifestations, with various neuropsychiatric characteristics, including tremors, transient aphasia, seizures, altered consciousness, myoclonus, cognitive impairment, and psychiatric manifestations. The hallmark presenting feature is a non-specific encephalopathy characterized by alteration of mental status and consciousness ranging from confusion to coma and impaired cognitive function, while those with cerebellar ataxia as the main manifestation is rare. We reported a case of Hashimoto's encephalopathy with cerebellar ataxia as the main manifestation, elevated anti-thyroid antibodies (anti-TPO/TG), and normal thyroid function. The symptoms of cerebellar ataxia improved after steroid treatment. Meanwhile, we reviewed the clinical features of 20 representative cases of HE with cerebellar ataxia as the core symptoms. In conclusion, based on our case findings and literature review, the diagnosis of HE should be suspected in cases of encephalopathy without an obvious cause, to quickly start an effective treatment.